Pengembangan Sistem Informasi Manajemen Produk Frozen Food PT. Fresh Food Indo - Felix Yosa Herdima Sanjaya; Yusi Tyroni Mursityo; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Fresh Food Indo is a company engaged in livestock agribusiness. There are several problems that affect a company's performance, one of which is the recording of goods data is still done by writing it on paper. Therefore, an effective and efficient product management information system is needed to be able to improve business processes at PT. Fresh Food Indo. The research method use Rational Unified Process (RUP). In the inception phase, it do as-is modeling and proposed business process modeling (to-be). The results of the analysis of business processes as-is obtained sales business processes and addition of goods and for the results of to-be analysis obtained sales business processes, addition of goods, and return of damaged goods. In the elaboration phase, requirements analysis and system design were carried out which produced 26 functional requirements and 1 non-functional requirement. In the construction phase is to implement and test the system. System implementation produces a web-based Product Management Information System. Validation testing does 17 tests with all valid results. Compatibility testing produces a product management system that has no problems. The last phase is the transition phase where this phase is tested by User Acceptance Testing (UAT). UAT results on the five respondents included the criteria of